EXPERIMENTAL-THEORETICAL PRINCIPLES OF AUTOMATIC DEFORMATION MONITORING SYSTEMS USING FIBER-OPTICAL ELEMENTS - Shardakov, I.N.; Sozonov, N.S.; Tsvetkov, R.V. (Perm Federal Research Centre Journal, 2016)
In the project the experimental and theoretical methods and approaches, which provided the development and creation of the automated deformation monitoring systems based on fiber-optical elements, are used. Experimental and theoretical studies on different scales were performed: from the sensing element to the extended monitoring object. Mathematical models (in the framework of the linear theory of elasticity) of the mechanical interaction of the elements of optical fiber sensors are both described: between each other and with the surface of the researched object. These models allowed carrying out the choice of parameters for experiments on the uniform-strength beam, to define the ways of fiber fastening to the substrate and the substrate to the researched object surface; to establish the level of temperature strains in the optical fiber sensor. The experimental studies of thermo mechanical characteristics were conducted for both: separate elements of the sensor (Bragg grating, glue joints), and for the fiber optical sensor in general under force and temperature influences. The results of these studies have established such sensor parameters as relative accuracy, sensitivity and «zero maintenance». It also established a constructive scheme of the fiber-optic strain sensor which allows recording the strains on the investigated surface.